A structural decomposition analysis of “Latin American decade” for selected countries - Tahsin, Emine (Asian Journal of Empirical Research, 2023)
The 2003-2014 period for Latin America refers to the recent boom period within the growth cycles of the region and is called as “Latin American decade”. Given that, the purpose of the paper is to analyze this specific period based on structural transformation dynamics. In this context, structural decomposition methods are evaluated to outline structural transformation patterns. For this analysis, the Groningen Growth and Development Centre (GGDC) Economic Transformation Database (ETD), which provides annual data on employment and real value added by 12 sub-sectors, is used for 8 LA countries (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Peru). The decomposition analysis is applied for three main periods (1990-2018, 1990-2003 and 2003-2014) within the growth cycles of the region. So it is predicted to define whether the “Latin American decade” differs from the previous period, regarding structural dynamics. During the “Latin American decade”, the region has gone commodity-led growth pattern and deindustrialization. Moreover, this pattern is not so homogenous. Specifically, the mining sector and non-tradeable sectors dominate the structural dynamics of some countries. Due to these patterns, the results underlie that productivity gains remained at low levels. Latin American countries need to design growth strategies that focus on escaping from productivity traps.